Jane Marcet’s lessons to the lesser educated about the political economy of foreign trade - Alexandra Sippel (XVII-XVIII, 2020)
This paper analyses Jane Marcet’s lessons about foreign trade in her two main pedagogical volumes. A disciple and friend of all the major thinkers who turned political economy into a science commanding as much respect as Newton’s, Marcet was a mouthpiece of choice to spread the word to the ladies, and then to the working classes. E.P. Thompson, among others, pointed out how Malthus was accused by the radical, working-class movements of de-moralising political economy. Marcet follows in her mentor’s footsteps, and this study suggests that not only does she take foreign trade (and hence luxury consumption) out of the realm of morals, but that in doing so, she takes away from ladies and workers alike their blossoming political role as conscientious consumers. Teaching political economy shows that Marcet recognised their intellectual capabilities, but teaching it as an incontrovertible science was also a way of silencing their claims, supposedly inspired by superficial sentiments rather than by sound reason.